The Application Of PCR RAPD Technique In Determining Female Sex Of Kapulasan (Nepheleum Lapaceum Mutabile) - Edi Wirman (Department of Crop Science, Faculty of Agriculture, Andalas University, 2019)
Kapulasan is one of horticultural plants derived from tropical region that has significant economic value. One of the obstacles in cultivating the plant is that kapulasan has flowering type of androdioceus, i.e. the male and the female flowers are separated. Female flowers produce hermaphroditic flowers that can produce fruits while the male ones will not produce fruits. In the cultivation of the plant, it is very difficult to determine the female flowers if they are propagated by seeds. It takes up to 7 years to determine the nature of the flowering. One of the important steps that can be done is through a system of early detection using molecular marks. RAPD technique as a simple technique can be used to distinguish the characteristics. The results of the research show that of the 250 primers used, the OPM-09 primer produces female sex bands related to the controller of the female kapulasan plants of which the ribbon produced is 512 bp in size.